2020
DOI: 10.1007/s00405-020-06383-z
|View full text |Cite
|
Sign up to set email alerts
|

Model for hands-on tonsillectomy surgical training of postgraduate residents during COVID-19 pandemic

Abstract: Purpose Otorhinolaryngological surgeries being highly aerosol-generating carry the risk of transmission of SARS-CoV-2. Most centers have canceled elective surgeries. Surgical demonstration and hands-on training of postgraduate residents are challenging during the COVID-19 pandemic. Continued training of residents is of utmost importance in terms of time and skill development. Tonsillectomy is one of the most common and important surgeries in ENT. Resident training of tonsillectomy is essential. Here, we presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Furthermore, postponing cases due to COVID-19 has had negative consequences not only for the health of patients but also for the training of the residents. 29 We also think that adenotonsillectomy, which is a basic operation in resident education, should be applied with these frameworks.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, postponing cases due to COVID-19 has had negative consequences not only for the health of patients but also for the training of the residents. 29 We also think that adenotonsillectomy, which is a basic operation in resident education, should be applied with these frameworks.…”
Section: Discussionmentioning
confidence: 99%
“…With these challenges faced by Otolaryngology residents, the need for simulation models has become more apparent for developing skills that include otomicroscopy, myringotomy and ventilation tube insertion. [11][12][13] A recent international survey of Otolaryngologists during the Covid-19 pandemic reported that 90 percent of respondents supported the use of surgical simulation in training. However, many did not have access to these tools at their institutions.…”
Section: Discussionmentioning
confidence: 99%